2020
DOI: 10.3390/safety6040044
|View full text |Cite
|
Sign up to set email alerts
|

Teenage Drivers’ Views of a Classroom and Closed-Road Post-License Advanced Driving Program, Guard Your Life

Abstract: In the US, teenage drivers have an increased risk of being involved in crashes. To address this, post-license advanced driving programs have emerged. This study gains teenagers’ perspective of a post-license defensive driving program focused on a hands-on introduction to emergency braking, skid recovery and the dangers of distracted driving. The teenagers completed a survey immediately following the program and a phone interview three months later. The open-ended survey and phone interview items reflect the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The results of the survey suggest that learning about ABS was one of the most important topics the teens learned about during the program, both directly after the program and three months later. The results of the phone interview suggest that participants avoided crashes and used the skills related to ABS braking within three months after the program [24]. Parents are required to stay for the classroom portion of the GYL program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the survey suggest that learning about ABS was one of the most important topics the teens learned about during the program, both directly after the program and three months later. The results of the phone interview suggest that participants avoided crashes and used the skills related to ABS braking within three months after the program [24]. Parents are required to stay for the classroom portion of the GYL program.…”
Section: Discussionmentioning
confidence: 99%
“…The GYL program utilizes a subset of the classroom information on ABS and ABS exercise as the car control classes in the current study. Though the survey studies [24,25] do not provide ABS performance information, these studies surveyed a population of teens and parents enrolled in a half day driving program with essentially double the group size. Not many of the parents surveyed from the GYL program had been trained to activate ABS, nor did many use hands-on techniques to teach their teen about ABS [25].…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 15 18 The main recommendation of other published evaluations is to focus YDs training on hazard anticipation and avoid emergency situations altogether. 10 , 15 , 17 , 19 …”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 11 , 19 These studies reported mixed effects on YD attitudes, driving behaviors, and driving record outcomes. 8 , 11 , 15 19 Participants of ADT programs did not show significantly improved driving records over time compared with the general population of YDs or a control group; however, there was also no evidence of less safe driving behavior. 8 , 9 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation